2017
DOI: 10.1080/09593330.2017.1393015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cyanide biodegradation by immobilized crude extract ofRhodococcusUKMP-5M

Abstract: The capability of the crude extract of Rhodococcus UKMP-5M was enhanced by adopting the technology of immobilization. Among the matrices screened to encapsulate the crude extract, gellan gum emerged as the most suitable immobilization material, exceeding the activity of cyanide-degrading enzyme by 61% and 361% in comparison to alginate carrier and non-immobilized crude extract, respectively. Improved bead mechanical strength which supported higher biocatalyst activity by 63% was observed when concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Gellan gum is an ionic heteropolysaccharide. It is also believed able to be used repetitively up to 20 batches without substantial loss of catalytic activity [44]. This proves that the durability of the beads is above adequate.…”
Section: Reusability Of the Immobilized Beadsmentioning
confidence: 85%
See 1 more Smart Citation
“…Gellan gum is an ionic heteropolysaccharide. It is also believed able to be used repetitively up to 20 batches without substantial loss of catalytic activity [44]. This proves that the durability of the beads is above adequate.…”
Section: Reusability Of the Immobilized Beadsmentioning
confidence: 85%
“…In the study, immobilized Pseudomonas luteola with calcium alginate, k-carrageenan and polyacrylamide can be reused up to four times with 75, 85 and 80% of dye decolorization [43]. Another study has shown that the gellan gum immobilized beads were able to be reused up to 20 times without substantial loss of catalytic activity [44]. No data was available on the reusability of gellan gum immobilized cells in Metanil Yellow dye decolorization.…”
Section: Reusability Of the Immobilized Beadsmentioning
confidence: 99%
“…Cell leakage as well as the free cell content immobilized on both support matrices after encapsulation were quantified by calculating the dry cell weight. Immobilization yield was determined following protocols described in [9] by substituting protein content with dry cell weight.…”
Section: G Decolourization Of Methylene Blue By Resting Cells and Immentioning
confidence: 99%
“…This immobilization matrix has better rheological characteristics in comparison to that of agar and carrageenan gels when assessed at similar concentrations [8]. Besides, the hydrogels are able to sustain stability over a broad pH range which is from 2 to 10 [9]. Gellan gum can be used as a simple matrix for enzyme immobilization due to its polyelectrolyte property, hydrophilicity, emulsification attributes, its non-hazardous features, biocompatibility and biodegradability [7].…”
Section: Introductionmentioning
confidence: 99%